Factor Influencing E-Cigarette Use and Its Impact on Adolescent Lung Health: Literature Review - Aisyah, Weni Nur; Rahayu, Amrita Cahyani; Jasmine, Devrina; Ciptaningrum, Anggraeni Dian; Herbawani, Chahya Kharin (Miracle Journal of Public Health, 2024)
The use of e-cigarettes among adolescents continues to increase, even though these cigarettes contain harmful substances that can cause lung disease. This study aims to evaluate the factors influencing adolescents' behavior in using e-cigarettes and their impact on lung health. This study used the literature review method with PRISMA guidelines. Literature was obtained from Google Scholar, PubMed, and ScienceDirect, with inclusion criteria being publications from 2019-2024 that focused on adolescents in developed and developing countries. A total of 15 articles were analyzed with exclusion criteria such as duplication, irrelevant literature, and inaccessibility. The results showed that adolescents' behavior is influenced by internal factors, such as knowledge, confidence, and gender, as well as external factors, such as parental support, peer environment, and accessibility. The misperception that e-cigarettes are safer than conventional cigarettes increases their use. Health impacts include asthma, wheezing, chronic cough, shortness of breath, chest pain, and EVALI (E-cigarette or Vaping Associated Lung Injury). Preventive and promotive interventions are needed to reduce the prevalence of e-cigarettes among adolescents through health risk education and strengthening social roles.